2017
DOI: 10.3390/jmse5040057
|View full text |Cite
|
Sign up to set email alerts
|

Regime Changes in Global Sea Surface Salinity Trend

Abstract: Abstract:Recent studies have shown significant sea surface salinity (SSS) changes at scales ranging from regional to global. In this study, we estimate global salinity means and trends using historical SSS data from the UK Met Office Hadley Centre objectively analyzed monthly fields and recent data from the SMOS satellite (2010)(2011)(2012)(2013)(2014). We separate the different components (regimes) of the global surface salinity by fitting a Gaussian Mixture Model to the data and using expectation-maximizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Since AR5, new and extended multi-decadal analyses have strengthened the observational support for increased contrast between high and low near-surface salinity regions and inter-basin contrast since the mid-20th century (Section 9.2.2.2; Durack and Wijffels, 2010;Good et al, 2013;Skliris et al, 2014;Aretxabaleta et al, 2017;Cheng et al, 2020). These analyses employ different statistical algorithms for interpolation, and only 1.3.5 and 8.3.1.1).…”
Section: Ocean Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since AR5, new and extended multi-decadal analyses have strengthened the observational support for increased contrast between high and low near-surface salinity regions and inter-basin contrast since the mid-20th century (Section 9.2.2.2; Durack and Wijffels, 2010;Good et al, 2013;Skliris et al, 2014;Aretxabaleta et al, 2017;Cheng et al, 2020). These analyses employ different statistical algorithms for interpolation, and only 1.3.5 and 8.3.1.1).…”
Section: Ocean Salinitymentioning
confidence: 99%
“…These analyses employ different statistical algorithms for interpolation, and only 1.3.5 and 8.3.1.1). However, this assessment is complicated by changing observational techniques (Section 1.5.1), temporally and spatially inhomogeneous sampling and uncertainties in interpolation algorithms and the substantial influence of modes of natural variabiltity and ocean circulation processes over interannual timescales (Skliris et al, 2014;Durack, 2015;Grist et al, 2016;Aretxabaleta et al, 2017;Vinogradova and Ponte, 2017;Liu et al, 2020). Following AR5, based on the updated analysis from Durack and Wijffels (2010) which infills in situ gaps to recover large-scale patterns the mean salinity contrast between high-and low-near-surface salinity regions increased by 0.14 [0.07 to 0.20] from 1950 to 2019.…”
Section: Ocean Salinitymentioning
confidence: 99%
“…Differences in osmotic pressure impede marine–freshwater transitions, and as a consequence, transitions are generally rare, occur on longer evolutionary timescales [ 2 , 3 ], and have led to repeated bursts of diversification in freshwater environments [ 4 ]. Identifying the processes underlying marine–freshwater habitat transitions is fundamental to our understanding of lineage diversification and habitat structuring on evolutionary timescales [ 5 ], as well as short-term adaptive potential to climate change as melting ice caps, altered precipitation patterns, and changes in oceanic currents result in freshening of large regions and local changes in the seasonal or annual cycling of salinity regimes [ 6 , 7 ]. Permanent establishment of ancestrally marine organisms in freshwaters depends on the ability of individual colonists to survive the initial hypoosmotic stress, acclimate to low salinity, and ultimately adapt to their new environment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A multidecadal study on linear trends of global ocean salinity patterns (Durack and Wijffels, 2010) reported surface salinity increases in all oceans, especially at evaporation-dominated subtropical gyres. A more recent study (Aretxabaleta et al, 2017), also reports salinification of the Atlantic Ocean consistent with CC-induced changes in global hydrological cycle. Future SLR-scenarios for estuaries around the world include increases in estuarine salinity, estuarine water residence time, tide range, stratification, and tidal prism volume (Costa et al, 2023).…”
Section: Introductionmentioning
confidence: 69%